Kinetic chain application to the dolphin kick in butterfly swimming - Wang, N.; Liu, Y.-T. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
This study examined the difference in underwater dolphin kick movement between elite and non-elite swimmers. Ten elite and ten non-elite swimmers participated in this study. Kinematic data from the sagittal view were collected and analyzed. Significant differences were found in the peak angular velocities of the lower trunk, thigh, and shank between the elite and the non-elite athletes. Additionally, the analyses on the peak angular velocity transfer rate between the connected segments showed a significant interaction between the skill level and the transfer rate. The findings are discussed in relation to the principle of kinetic chains. We conclude that the optimal propulsion during the downbeat part of the dolphin kick is reached when most segments participated in the movement.